Enactive Systems & Computing Mapping the terrain for Human-Computer Interaction research - Arpetti, Alessandro; Baranauskas, M. Cecília C. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2016: Anais do XLIII Seminário Integrado de Software e Hardware, 2016)
While the concept of enaction is not new, recent trends on the use of contemporary devices to interact with computational systems have attracted the attention in the field of interaction design. A quick look in the literature reveals different meanings for an enactive system, depending on the knowledge domain. This paper explores the subject by conducting a Systematic Literature Review to construct a big picture on the subject. Results reveal the paths being traced and issues still unexplored that offer opportunities for investigation in the human computer interaction field.